Conformal field theory and the hot phase of three-dimensional U(1) gauge theory - Michele Caselle; Alessandro Nada; Marco Panero; Davide Vadacchino (Journal of High Energy Physics, 2019)
Abstract We study the high-temperature phase of compact U(1) gauge theory in 2 + 1 dimensions, comparing the results of lattice calculations with analytical predictions from the conformal-field-theory description of the low-temperature phase of the bidimensional XY model. We focus on the two-point correlation functions of probe charges and the field-strength operator, finding excellent quantitative agreement with the functional form and the continuously varying critical indices predicted by conformal field theory.